2005
DOI: 10.14742/ajet.1314
|View full text |Cite
|
Sign up to set email alerts
|

Rochester Castle MMORPG: Instructional gaming and collaborative learning at a Western Australian school

Abstract: This paper reports on the first stage of a project to develop and test the use of massively multiplayer online role playing games (MMORPGs) for promoting computer supported collaborative learning through instructional gaming in the high school classroom. Teachers and students of English and Science at Swan View Senior High School, Western Australia were involved in a pilot study as "proof of concept", in which they participated in both game design and game play within a MOO based collaborative virtual environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…A major aspect of MMORPGs is these interactions, which enable collaborative exchanges of thoughts, emotions, and ideas among the game players (Brown 1994). Most of the interactions, which develop as players participate in MMORPGs, take place in the form of language and language skills, and this may be why MMORPGs evolving out of multi‐user dungeons have been applied to educational environments (Lee et al . 2005; Lee & Hoadley 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major aspect of MMORPGs is these interactions, which enable collaborative exchanges of thoughts, emotions, and ideas among the game players (Brown 1994). Most of the interactions, which develop as players participate in MMORPGs, take place in the form of language and language skills, and this may be why MMORPGs evolving out of multi‐user dungeons have been applied to educational environments (Lee et al . 2005; Lee & Hoadley 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A major aspect of MMORPGs is these interactions, which enable collaborative exchanges of thoughts, emotions, and ideas among the game players (Brown 1994). Most of the interactions, which develop as players participate in MMORPGs, take place in the form of language and language skills, and this may be why MMORPGs evolving out of multi-user dungeons have been applied to educational environments (Lee et al 2005;Lee & Hoadley 2006). The applicable principle of teaching and learning behind MMORPGs might be the very fact that at any time thousands of participants can be online interacting with one another at the same time, engaging in a 3D online representation of actual locations (Childress & Braswell 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research (e.g., Faust, Meyer & Griffiths, 2013;) has shown that gamers claim to have learned such things as team working skills and computer skills from online gaming. Similarly research by Lee, Eustace, Fellows, et al (2005) reported that students who played an educational MMORPG gained new skills in collaborating online (something which is inherent in most MMORPGs). The evidence presented in the current study and previous research reveals that MMORPGs could potentially be used in educational contexts as has been demonstrated elsewhere (e.g., de Freitas & Griffiths, 2008).…”
Section: Social Interactionmentioning
confidence: 89%
“…Gee also highlighted similarities between models of learning in education and game mastery [4], the capacity for games to support deep learning [5] and offering a safe environment where the consequences of failure are lower than in traditional education approaches [2]. Lee et al [6] extended on Gikas and Van Eck [7] and mapped gaming genre and activities across Gagne's intellectual skills [8] and Bloom's taxonomy of the cognitive domain [9]. In this context, MMORPGs provide the added benefit of engaging large groups of remotely located users [10] and, through their design, facilitate collaborative learning approaches [11].…”
Section: Introductionmentioning
confidence: 99%
“…They also offer the opportunity to collaboratively engage students with a wide range of learning domains and convey experiential learning [12] through an immersive simulation environment. For instance, Second-Life has been widely used in various educational disciplines [13] and Lee et al [6] investigated a Massively Multi-Player Online approach (MMO) towards supporting English [14] and History education in the Rochester Castle MMORPG [15].…”
Section: Introductionmentioning
confidence: 99%